Small Governing Coalition in Hong Kong and its Impact on Political Freedom - Trystanto Trystanto (Jurnal Sentris, 2023)
Hong Kong has seen an upheaval in recent years. From the protests over the extradition law to the protests over the National Security Law, these protests are a response to the ever-encroaching hand of Beijing on political rights in Hong Kong. After the National Security Law was implemented, Hong Kong’s freedom was almost gone. One by one, pro-democracy protesters, opposition parliament members, and opposition media are being targeted and repressed. Despite the numerous protests and riots, the Hong Kong SAR government perseveres with little concession to the protesters. Why does the government of Hong Kong decided not to respect Hong Kong’s unique democratic system in China, arguably the system that has brought Hong Kong to one of the most prominent cities in the world for global interactions, and instead wish to turn it into another normal Chinese city? Why does the Hong Kong SAR government almost completely ignore the voice of the Hong Kong people? Using the framework developed by Bruce Bueno de Mesquita and Alastair Smith in The Dictator’s Handbook, I argue that the small size of Hong Kong’s governing coalition (i.e., the minimum amount of support required for the leader to stay in power) and the ease in which the Chief Executive of Hong Kong rewards her allies play a significant role in this democratic backsliding. Furthermore, while the Western World reacted in outrage over this undemocratic encroachment of Beijing on Hong Kong, I argue that their sanctions on Hong Kong leaders will not play a significant role as the Chief Executive of Hong Kong does not need their support.  Keywords: Hong Kong; democracy; protests; governing coalition;sanctions REFERENCES   Allison, Graham. Destined for War: Can America and China Escape the Thucydides’s Trap? New York: Houghton Miflin Harcourt Publishing Company, 2017.  Associated Press. “Only Hand-Picked Pro-Beijing ‘Patriots’ Get to Vote for Committee That Will Choose Hong Kong’s next Government.” The Globe and Mail, September 19, 2021. https://www.theglobeandmail.com/world/article-hong-kong-voters-to-choose-new-election committee-under-pro-beijing/.  BBC News. “North Koreans Vote in ‘No-Choice’ Parliamentary Elections.” BBC News, March 10, 2019. https://www.bbc.com/news/world-asia-47492747. Bloomberg News. “Xi Finalizes Hong Kong Election Changes, Cementing China Control.” Bloomberg, March 30, 2021. https://www.bloomberg.com/news/articles/2021-03- 30/china-to-form-small-group-to-vet-hong-kong-elections-scmp-says.  Candice Chau. “Hong Kong Democratic Party May Breach Security Law If It Tells Members Not to Run in Election, Warns Pro-Beijing Figure.” Hong Kong Free Press, September 6, 2021. https://hongkongfp.com/2021/09/06/hong-kong-democratic-party-may-breach-security-law if-it-tells-members-not-to-run-in-election-warns-pro-beijing-figure/.  CBS News. “Hong Kong Protesters Arrested as Trump Vows to Act ‘Powerfully’ against China.” www.cbsnews.com, May 27, 2020. https://www.cbsnews.com/news/hong-kong-protesters arrested-riot-police-china-2020-05-27/.  Chen, Jiawen. “Why Economic Sanctions on North Korea Fail to Work?” China Quarterly of International Strategic Studies 03, no. 04 (January 2017): 513–34. https://doi.org/10.1142/s2377740017500300.  Cox, Gary. Making Votes Count: Strategic Coordination in the World’s Electoral Systems. Cambridge: Cambridge University Press, 1992.  Drezner, Daniel W. “The United States of Sanctions: The Use and Abuse of Economic Coercion.” Foreign Affairs 100, no. 5 (2021): 142–54. https://www.foreignaffairs.com/articles/united-states/2021-08-24/united-states-sanctions.  Foreign, Commonwealth, and Development Office, and Export Control Joint Unit. “UK Arms Embargo on Mainland China and Hong Kong.” GOV.UK, December 31, 2020. https://www.gov.uk/government/collections/uk-arms-embargo-on-mainland-china-and-hong kong.   Government of Hong Kong Special Administrative Region. “Government Structure.” GovHK, September 2021. https://www.gov.hk/en/about/govdirectory/govstructure.htm. Grant, Charles. “Russia, China, and Global Governance.” London: Centre for European Reform, 2012. https://carnegieendowment.org/files/Grant_CER_Eng.pdf.  Grundy, Tom. “‘Highly Necessary’: Beijing to Discuss Enacting National Security Law in Hong Kong Following Months of Protest.” Hong Kong Free Press, May 21, 2020. https://hongkongfp.com/2020/05/21/breaking-beijing-to-discuss-enacting-national-security law-in-hong-kong-following-months-of-protest/.  Hathaway, Oona A, and Scott J Shapiro. The Internationalists: How a Radical Plan to Outlaw War Remade the World. New York: Simon & Schuster Paperbacks, 2017.  Kirby, Jen. “Pro-Democracy Candidates Dominate Hong Kong’s Local Elections in a Rebuke to China.” Vox, November 25, 2019. https://www.vox.com/2019/11/25/20981691/hong-kong district-council-elections-pro-democracy.  Kuo, Lily, and Verna Yu. “Hong Kong Protests: Carrie Lam Denies Offering to Resign.” The Guardian, September 3, 2019. https://www.theguardian.com/world/2019/sep/03/hong-kong protests-carrie-lam-denies-she-considered-resigning.  Leung, Christy. “Extradition Bill Not Made to Measure for Mainland China and Won’t Be Abandoned, Hong Kong Leader Carrie Lam Says.” South China Morning Post, April 2019. https://www.scmp.com/news/hong-kong/politics/article/3004067/extradition-bill-not-made measure-mainland-china-and-wont. Lo, Chloe. “Hong Kong Leader’s Approval Rating Falls to Lowest since Sept.” Bloomberg, February 17, 2021. https://www.bloomberg.com/news/articles/2021-02-17/hong-kong-leader-s approval-rating-falls-to-lowest-since-sept.  Low, Zoe. “What Sparked Hong Kong’s Biggest Mass Arrests under National Security Law?” South China Morning Post, January 6, 2021. https://www.scmp.com/news/hong kong/politics/article/3116586/hong-kong-national-security-law-35-plus-ambition-colour.  Mahbubani, Kishore, and Jeffery Sng. The ASEAN Miracle: A Catalyst for Peace. Singapore: National University of Singapore Press, 2017.  Mahbubani, Kishore. Has China Won? The Chinese Challenge to American Primacy. New York: PublicAffairs, 2020.  Mahtani, Shibani, Tiffany Liang, Anna Kam, and Simon Denyer. “Hong Kong’s Pro-Democracy Parties Sweeping Pro-Beijing Establishment aside in Local Elections.” The Washington Post, March 30,2020. https://web.archive.org/web/20200330160031/https://www.sfchronicle.com/news/article/Record-turnout-in-Hong-Kong-election-seen-as-a-14858897.php.  Mesquita, Bruce Bueno de, and Alastair Smith. The Dictator’s Handbook : Why Bad Behavior Is Almost Always Good Politics. New York: Public Affairs, 2012.  Olorunnipa, Toluse. “As Trump Puts Partisan Spin on Federal Aid for States, Republicans and Democrats Warn of Coming Financial Calamity.” Washington Post, April 27, 2020. https://www.washingtonpost.com/politics/as-trump-puts-partisan-spin-on-federal-aid-for states-republicans-and-democrats-warn-of-coming-financial-calamity/2020/04/27/a542f19e 889a-11ea-8ac1-bfb250876b7a_story.html.  Registration and Electoral Office of the Government of Hong Kong Special Administrative Region. “REO : Who May Register / How to Register - Functional Constituencies.” Reo.gov.hk. Accessed October 19, 2021. https://www.reo.gov.hk/en/voter/FC.htm.  Reuters. “U.S. Condemns ‘Unjustified Use of Force’ in Hong Kong: Senior Official.” Reuters, November 18, 2019, sec. Emerging Markets. https://www.reuters.com/article/us-hongkong protests-usa-idUSKBN1XS06A.  ———. “U.S. Condemns China’s New Security Law for Hong Kong, Threatens Further Actions.” Reuters, June 30, 2020, sec. APAC. https://www.reuters.com/article/us-china hongkong-security-usa-idUSKBN2412N9.  Roantree, Anne Marie, Greg Torode, and James Pomfret. “Special Report: Hong Kong Leader Says She Would ‘Quit’ If She Could, Fears Her Ability to Resolve Crisis Now ‘Very Limited.’” Reuters, September 3, 2019. https://www.reuters.com/article/us-hongkong protests-carrielam-specialre-idUSKCN1VN1DU.  Sanjaya, Trystanto. “Analyzing the ‘Democracy vs. Autocracy’ Advocacy of the Biden Administration in the Upcoming US-China Great Power Competition from the Perspective of National Interest .” Tamkang Journal of International Affairs 26, no. 4 (2023): 47–98.  Subcommittee on Decision of the National People's Congress on Improving the Electoral System of the Hong Kong Special Administrative Region. The Amended Annex I and Annex II to Basic Law, LC Paper No. CB(4)703/20-21(01) § (2021). https://www.legco.gov.hk/yr20- 21/english/hc/sub_com/hs102/papers/hs10220210331cb4-703-1-e.pdf.  Tong, Kurt. “Hong Kong and the Limits of Decoupling.” Foreign Affairs, July 26, 2021. https://www.foreignaffairs.com/articles/asia/2021-07-14/hong-kong-and-limits-decoupling. United Nations Treaty Collection, Joint Declaration of the Government of the United Kingdom of Great Britain and Northern Ireland and the Government of the People's Republic of China on the Question of Hong Kong, Vol. 1399, (New York, 1994), 62  United States Department of the Treasury. “Treasury Sanctions Individuals for Undermining Hong Kong’s Autonomy | U.S. Department of the Treasury.” home.treasury.gov, August 7, 2020. https://home.treasury.gov/news/press-releases/sm1088.  Weeks, Jessica L.P. Dictators at War and Peace. Ithaca: Cornell University Press, 2014. Xinhua. “Hong  Kong Must Be Governed by Patriots.” Global TImes, November 12, 2020. https://www.globaltimes.cn/content/1206580.shtml.  香港中联办. “中华人民共和国香港特别行政区基本法附件二香港特别行政区立法会的产生办法和表 决程序.” Hong Kong Liaison Office, March 30, 2021. https://mp.weixin.qq.com/s/h6q6yzNwNXuJZ55bx98lFQ.